Letramento literário na escola: a adaptação dos clássicos na formação do leitor literário - Luciana Aparecida de Paula Silva (2018)
The formation of the literary reader and the space of literature in the classroom, especially in the public school, has been discussed for many years and few changes have actually occurred in his teaching. Considering what Cosson (2010) advocates on the essentiality of literature in the formation of the reader and on the school's duty to work properly on literary reading this dissertation presents a proposal for the development of literary literacy of the student. Held at the E. E. Mauro Faccio Gonçalves in Sete Lagoas, the qualitative research was attended by students from two groups of nine years. The aim of the research was to investigate the role and efficacy of reading classic works adapted as a step in the development of the literary reader 's formation of Elementary School and in the construction of his literary literacy. We tried to answer the following question: to what extent can a teaching project based on readings of classical works adapted for the youth audience offer more possibilities for advancement in the literary literacy of the students and the consequent formation of the reader of literature? The information were produced by questionnaires, class recording, reflective diary and portfolio with activities produced by the students. The strategy of mediation of the activities was the Literary Literature proposed by Cosson (2014). The reading of excerpts from literary classics originals was compared before, and after the reading of the adapted works, that attested, that the teacher's mediation connected with the reading of the adaptation, and the capacities powered by the students in the readings of the works are configured as an access for more readings dense, like that of a classic, by making possible a first contact with the composition. This work is an invitation for Portuguese-speaking teachers to turn their eyes to the teaching of literature, after learning to read literature, the student frees himself from physical limitations and humanizes himself.